Efektifitas penerapan media audiovisual pada mobilisasi dini pasien post operasi - Sagita, Icha; Sunarsih, Sunarsih; Rihiantoro, Tori (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Based on interviews with postoperative patients in the general surgery and digestive wards of General Ahmad Yani Metro Hospital, many are reluctant to undergo early mobilization due to a lack of knowledge from both patients and their families. This lack of knowledge regarding postoperative patient care, particularly regarding early mobilization, leads to a lack of early mobilization practices, which can increase the risk of postoperative complications. Purpose: To provide an overview and effectiveness of audiovisual applications in early mobilization of postoperative patients. Method: This activity is a quantitative quasi-experimental study with a non-equivalent control group design approach. The goal is to provide an overview of the application of audiovisual media in the implementation of early mobilization in postoperative patients. The data population is the total number of surgical procedures at General Ahmad Yani Metro Hospital, Lampung Province from January to December 2023, which is 6,678, with an average of 557 surgical procedures per month. Sampling using non-probability sampling with a purposive sampling technique obtained 60 postoperative patients with general anesthesia. Respondents are grouped into 2 groups, where the control group carried out early mobilization with conventional educational instructions or hospital service standards while the intervention group received audiovisual media instructions (educational videos/animations). Measurements used an observation questionnaire with a checklist of each stage of the respondent's early mobilization activities. As an evaluation, data were analyzed using chi-square test statistics to see the effectiveness of audiovisual education on the implementation of early mobilization. Results: 25 (83.3%) respondents in the intervention group were categorized as good, while 5 (16.7%) were categorized as poor. Meanwhile, 12 (40.0%) respondents in the control group were categorized as good, while 18 (60.0%) were categorized as poor. The chi-square test for early mobilization implementation in the intervention and control groups yielded a p-value of 0.001 and an OR of 7.500. 25 (67.6%) respondents in the intervention group were categorized as good, while 12 (32.4%) respondents in the control group were categorized as poor. 5 (21.7%) respondents in the intervention group were categorized as poor, while 18 (78.3%) respondents in the control group were categorized as poor. Conclusion: The application of audiovisual media in early mobilization of postoperative patients significantly improved patient knowledge and understanding of proper early mobilization implementation. Implementing early mobilization with audiovisual media contributed to a 7.5-fold increase in the likelihood of success. Suggestion: It is hoped that future researchers can conduct similar studies involving other variables such as patient anxiety levels, family support, or patient education levels, as well as with a larger and more diverse sample to obtain generalizable results. Keywords: Audiovisual; Early mobilization; Health education; Postoperative patients Pendahuluan: Berdasarkan wawancara pasien pasca operasi di ruang bedah umum dan digestif RSUD Jendral Ahmad Yani Metro banyak yang enggan melakukan mobilisasi dini karena kurangnya pengetahuan pasien maupun keluarga. Minimnya pengetahuan pasien maupun keluarga tentang perawatan pasien pasca operasi terutama tentang mobilisasi dini pasien pasca operasi menyebabkan kurangnya pelaksanaan mobilisasi dini pasca operasi yang dapat meningkatkan resiko terjadinya komplikasi pasca operasi. Tujuan: Untuk memberikan gambaran dan efektifitas penerapan audiovisual pada pelaksanaan mobilisasi dini pasien post operasi. Metode: Kegiatan ini adalah penelitian kuantitatif quasi-eksperiment dengan pendekatan non-equivalent control group design. Sasarannya adalah memberikan gambaran mengenai penerapan media audiovisual dalam pelaksanaan mobilisasi dini pada pasien post operasi. Populasi data adalah jumlah seluruh tindakan operasi di RSUD Jendral Ahmad Yani Metro Provinsi Lampung dari Januari-Desember 2023 yaitu sebanyak 6.678, dengan rata-rata 557 tindakan operasi per bulan. Pengambilan sampel secara non-probability sampling dengan teknik purposive sampling mendapatkan 60 pasien pasca operasi dengan general anestesi. Responden di kelompokan menjadi 2 group, dimana kelompok kontrol melakukan mobilisasi dini dengan petunjuk edukasi konvensional atau standar pelayanan rumah sakit sedangkan kelompok intervensi mendapatkan petunjuk media audiovisual (video edukasi/animasi). Pengukuran menggunakan kuesioner observasi dengan pengisian berupa ceklist dari setiap tahapan aktifitas mobilisasi dini responden. Sebagai evaluasi, data di analisa menggunakan statistik chi square test untuk melihat efektifitas edukasi audiovisual terhadap penerapan pelaksanaan mobilisasi dini. Hasil: Menunjukkan bahwa pelaksanaan mobilisasi dini responden pada kelompok intervensi yang dalam kategori baik adalah sebanyak 25 (83.3%) dan sebanyak 5 (16.7%) dalam kategori kurang. Sedangkan pada kelompok kontrol yang dalam kategori baik adalah sebanyak 12 (40.0%) dan sebanyak 18 (60.0%) dalam kategori kurang. Berdasarkan hasil uji chi-square terhadap pelaksanaan mobilisasi dini dari kelompok intervensi dan kontrol mendapatkan pValue=0.001 dan nilai OR=7.500, dimana kelompok intervensi yang memiliki kategori baik adalah sebanyak 25 (67.6%) dan kelompok kontrol sebanyak 12 (32.4%), sedangkan kelompok intervensi yang memiliki kategori kurang adalah sebanyak 5 (21.7%) dan kelompok kontrol sebanyak 18 (78.3%). Simpulan: Penerapan media audiovisual dalam mobilisasi dini pada pasien post operasi, sangat signifikan dalam meningkatkan pengetahuan dan pemahaman pasien tentang pelaksanaan mobilisasi dini dengan baik. Pelaksanaan mobilisasi dini dengan media audiovisual berkontribusi memiliki peluang 7.5 kali menjadi lebih baik. Saran: Diharapkan agar peneliti selanjutnya dapat melakukan penelitian serupa dengan melibatkan variabel lain seperti tingkat kecemasan pasien, dukungan keluarga, atau tingkat pendidikan pasien serta dengan sampel yang lebih besar dan beragam untuk mendapatkan hasil yang generalisasi.